Determinants Of Capital Adequacy Ratio Empirical Study of Banks Listed On The Indonesian Stock Exchange For The Period 2017 – 2022 - Veronika Fransiska; Indra Siswanti (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This study aims to determine the effect of bank size, loan to deposit ratio, operating expenses on operating income, return on assets and non-performing loans on capital adequacy ratio. This research was conducted at commercial banks listed on the Indonesia Stock Exchange for the period 2017-2022. The population in this study were 46 commercial banks. The sampling technique used in this study was purposive sampling, thus the sample used was 39 samples. The data were analyzed using panel data regression. The results showed that bank size has a positive and significant effect on capital adequacy ratio, loan to deposit ratio has a negative and significant effect on capital adequacy ratio, operating expenses operating income has a positive and significant effect on capital adequacy ratio, return on assets has no effect on capital adequacy and non-performing loans have no effect on capital adequacy ratio.